The embodied mind in motion: a neuroscientific and philosophical perspective on prevention and therapy of dementia - Dzwiza-Ohlsen, Erik N.; Kempermann, Gerd (Frontiers in Psychology, 2023)
The embodied mind in motion is a concept in which health and well-being, prevention and therapy, as well as lifestyle and habits meet. The mind changes profoundly in the course of dementias, affecting daily living and resulting in reduced quality of life. Interdisciplinary approaches are required for a holistic understanding of how the mind is affected by dementia. We here explore what such a holistic theory of dementia might look like and propose the idea of “embodied mind in motion”. The paradigm is biopsychosocial or biocultural, the theoretical anchor point is the lifeworld, and the guiding concept is “embodiment,” as body and mind are constantly in motion. Physical activity is, hence, central for the experience of health and well-being, beyond being “exercise” and “health behavior”. We discuss the embodied mind in motion referring to phenomenology, enactivism and (philosophical) anthropology. In our view, habits are embodied long-term memories and a philosophical equivalent to lifestyle. They unfold the meaningfulness of moving the body, complementing the objectifiable benefits of physical exercise. Empirical studies on “holistic activities” like hiking, yoga, music and dance illustrate improved integration into everyday life. Their meaningfulness enhances compliance and increases the preventive and even therapeutic potential. A crucial factor for this is the emotional dimension of lifestyle, exemplified by the virally popularized performance of “Swan Lake” by wheel-chair bound ex-ballerina Marta Cinta González Saldaña, suffering from Alzheimer’s disease. A number of epistemological and ontological consequences anchor “embodied movement” as a valuable principle for dementia research.